PENGARUH PERCEIVED VALUE DAN PRICE PERCEPTION TERHADA PURCHASE DECISION MELALUI TRUST PADA INDUSTRI MOBIL LISTRIK DI JAKARTA - Vincent Suwito; Rita Rita (Bajang Institute, 2026)
The development of the automotive industry, particularly electric vehicles, has shifted consumer behavior in purchase decision-making, influenced by perceived value and price perception. This study aims to analyze the effect of Perceived Value and Price Perception on Purchase Decision, with Trust as a mediating variable among electric vehicle consumers in Jakarta. A quantitative approach was applied using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. Data were collected from 210 respondents who are either potential buyers or current users of electric vehicles in Jakarta. The analysis results indicate that both Perceived Value and Price Perception have a positive and significant effect on Trust and Purchase Decision, with Trust proven to act as a partial mediator. The findings show that perceived value is the most dominant factor driving purchase decisions, followed by price perception and trust in the product. This study offers strategic implications for automotive industry players to focus on enhancing consumer value perception and trust to increase the conversion rate of electric vehicle purchases.